Categorical perception in animal communication and decision-making. (18th February 2020) - Green, Patrick A; Brandley, Nicholas C; Nowicki, Stephen
Abstract: The information an animal gathers from its environment, including that associated with signals, often varies continuously. Animals may respond to this continuous variation in a physical stimulus as lying in discrete categories rather than along a continuum, a phenomenon known as categorical perception. Categorical perception was first described in the context of speech and thought to be uniquely associated with human language. Subsequent work has since discovered that categorical perception functions in communication and decision-making across animal taxa, behavioral contexts, and sensory modalities. We begin with an overview of how categorical perception functions in speech perception and, then, describe subsequent work illustrating its role in nonhuman animal communication and decision-making. We synthesize this work to suggest that categorical perception may be favored where there is a benefit to 1) setting consistent behavioral response rules in the face of variation and potential overlap in the physical structure of signals, 2) especially rapid decision-making, or 3) reducing the costs associated with processing and/or comparing signals. We conclude by suggesting other systems in which categorical perception may play a role as a next step toward understanding how this phenomenon may influence our thinking about the function and evolution of animal communication and decision-making. Abstract : We synthesize research on categorical perception and show how it functions in animal communication and decision-making. Categorical perception—a process by which continuous variation in a stimulus is parsed into discrete perceptual categories—was originally thought unique to human speech perception. We outline how categorical perception is now seen as an important mechanism by which diverse animals make accurate, rapid, and less-costly decisions across a wide range of behavioral contexts.